2021
DOI: 10.1002/14651858.cd013157.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional supplementation for nonalcohol-related fatty liver disease: a network meta-analysis

Abstract: Al-Muzafar 2017Al-Muzafar HM, Amin KA. Probiotic mixture improves fatty liver disease by virtue of its action on lipid profiles, leptin, and inflammatory biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 295 publications
0
13
0
3
Order By: Relevance
“…αT, a well-known antioxidant with a key role against lipid peroxidation in NASH pathogenesis [ 118 ], has achieved highest results when combined with ascorbic acid [ 119 , 120 ]. However, the evidence lacks considerable certainty concerning the effects of nutritional supplementation compared to no additional intervention on all clinical outcomes for patients with NAFLD [ 121 ]. For that, we suggest further studies for exploring the benefits of OLE using (1) Verdeal and Madural leaves as affordable sources of PUFA; (2) Verdeal’s elementary leaves for optimal omega-6/omega-3 ratio; (3) Cobrançosa’s elementary leaves as an affordable source of α-T; and (4) Cobrançosa’s leaf sprouts for high TPC and potential to mimic statins or pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…αT, a well-known antioxidant with a key role against lipid peroxidation in NASH pathogenesis [ 118 ], has achieved highest results when combined with ascorbic acid [ 119 , 120 ]. However, the evidence lacks considerable certainty concerning the effects of nutritional supplementation compared to no additional intervention on all clinical outcomes for patients with NAFLD [ 121 ]. For that, we suggest further studies for exploring the benefits of OLE using (1) Verdeal and Madural leaves as affordable sources of PUFA; (2) Verdeal’s elementary leaves for optimal omega-6/omega-3 ratio; (3) Cobrançosa’s elementary leaves as an affordable source of α-T; and (4) Cobrançosa’s leaf sprouts for high TPC and potential to mimic statins or pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Early probiotic, prebiotic, symbiotic, and fecal microbiota transfer interventions may prevent NAFLD exacerbation ( 15 , 16 ). Meanwhile, some investigations have reported that the intake of dietary supplements (such as vitamin D, vitamin E, and fatty acid) ( 17 , 18 ) and functional foods (such as garlic powder, Nigella sativa , sumac powder, and olive oil) ( 19 23 ) may ameliorate and/or reverse NAFLD, which may be due to their antioxidant properties. For example, organosulfur compounds in garlic powder and flavonoids in green tea extract belong to the category of functional foods, but in terms of properties, they exhibit antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NAFLD has increased rapidly over the past three decades ( 1 , 2 ) and the number of people suffering from NAFLD are expected to be more than 100 million by 2030 ( 3 ). Usually, parallels to the prevalence of obesity, type 2 diabetes and cardiovascular disease, NAFLD decreases life expectancy and increases requirements of liver transplantation ( 4 , 5 ). Moreover, NAFLD progresses from steatosis, non-alcoholic steatohepatitis (NASH), to liver fibrosis and even ultimately to hepatocellular carcinoma ( 4 ), while approximately 20–30% of individuals may progress to NASH ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, parallels to the prevalence of obesity, type 2 diabetes and cardiovascular disease, NAFLD decreases life expectancy and increases requirements of liver transplantation ( 4 , 5 ). Moreover, NAFLD progresses from steatosis, non-alcoholic steatohepatitis (NASH), to liver fibrosis and even ultimately to hepatocellular carcinoma ( 4 ), while approximately 20–30% of individuals may progress to NASH ( 6 ). It is estimated that NASH prevalence will increase up to 56% by 2030 in the United States at a greater rate than the other European and Asian countries ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation